Identification of SOX2 Interacting Proteins in the Developing Mouse Lung With Potential Implications for Congenital Diaphragmatic Hernia - Schilders, Kim A. A.; Edel, Gabriëla G.; Eenjes, Evelien; Oresta, Bianca; Birkhoff, Judith; Boerema-de Munck, Anne; Buscop-van Kempen, Marjon; Liakopoulos, Panagiotis; Kolovos, Petros; Demmers, Jeroen A. A.; Poot, Raymond; Wijnen, Rene M. H.; et al. (Frontiers in Pediatrics, 2022)
Congenital diaphragmatic hernia is a structural birth defect of the diaphragm, with lung hypoplasia and persistent pulmonary hypertension. Aside from vascular defects, the lungs show a disturbed balance of differentiated airway epithelial cells. The Sry related HMG box protein SOX2 is an important transcription factor for proper differentiation of the lung epithelium. The transcriptional activity of SOX2 depends on interaction with other proteins and the identification of SOX2-associating factors may reveal important complexes involved in the disturbed differentiation in CDH. To identify SOX2-associating proteins, we purified SOX2 complexes from embryonic mouse lungs at 18.5 days of gestation. Mass spectrometry analysis of SOX2-associated proteins identified several potential candidates, among which were the Chromodomain Helicase DNA binding protein 4 (CHD4), Cut-Like Homeobox1 (CUX1), and the Forkhead box proteins FOXP2 and FOXP4. We analyzed the expression patterns of FOXP2, FOXP4, CHD4 and CUX1 in lung during development and showed co-localization with SOX2. Co-immunoprecipitations validated the interactions of these four transcription factors with SOX2, and large-scale chromatin immunoprecipitation (ChIP) data indicated that SOX2 and CHD4 bound to unique sites in the genome, but also co-occupied identical regions, suggesting that these complexes could be involved in co-regulation of genes involved in the respiratory system.